Early-Life Iron Deficiency and Subsequent Repletion Alters Development of the Colonic Microbiota in the Pig - Knight, Laura C.; Wang, Mei; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Nutrition, 2019)
Background: Iron deficiency is the most prevalent micronutrient deficiency worldwide, affecting over two billion people. Early-life iron deficiency may alter the developing microbiota, which may or may not be reversible with subsequent dietary iron repletion. Thus, the aim of this study was to determine whether early-life iron deficiency and subsequent repletion alter colonic microbial composition and fermentation end-product concentrations in pigs. Methods: Forty-two male pigs received either control (CONT, 21.3 mg Fe/L) or iron-deficient (ID, 2.72 mg Fe/L) milk replacer treatments from postnatal day (PND) 2 to 32. Subsequently, twenty pigs continued through a series of age-appropriate, iron-adequate diets from PND 33 to 61. Contents from the ascending colon (AC) and rectum (feces) were collected at PND 32 and/or 61. Assessments included microbiota composition by 16S rRNA sequencing and volatile fatty acid (VFA) concentrations by gas chromatography methods. Data were analyzed using a 1-way ANOVA and PERMANOVA to assess the main effects of early-life iron status on all outcomes. Results: In AC samples, 15 genera differed (P < 0.05) between ID and CONT pigs, while 27 genera differed (P < 0.05) in fecal samples at PND 32. Early-life ID pigs had higher (P = 0.012) relative abundance of Lactobacillus in AC samples compared with CONT pigs. In feces, ID pigs had lower (P < 0.05) relative abundances of Bacteroides and Clostridium from the families of Clostridiaceae, Lachnospiraceae, and Ruminococcaceae. At PND 61, only two genera differed between treatment groups in AC samples, with ID pigs having a higher (P = 0.043) relative abundance of Bifidobacterium and lower (P = 0.047) relative abundance of Prevotella. Beta diversity differed at PND 32 in both AC and feces between CONT and ID pigs but no differences remained at PND 61. At PND 32, the total VFA concentration was higher in ID pigs compared with CONT pigs in both AC (P = 0.003) and feces (P = 0.001), but no differences in VFA concentrations persisted to PND 61. Conclusion: Early-life iron status influenced microbial composition and VFA concentrations within the large intestine, but these differences were largely normalized following subsequent dietary iron repletion.